Smart Internet of things aided by“terminal-edge-cloud” cooperation - Dapeng WU; Puning ZHANG; Ruyan WANG (物联网学报)
The further expansion of the Internet of things (IoT) traffic and the explosive growth of the terminal data require higher delay performance and computing ability of the access network.The traditional wireless network architecture has been unable to support the rapid development of IoT.Thus,the edge-driven smart IoT architecture was proposed.Firstly,the main factors that restrict the development of IoT were analyzed,and then the edge computing technology was introduced into the IoT to form a “terminal-edge-cloud” cooperative computing architecture to deal with the traffic data efficiently and timely.Finally,the challenges of the edge-driven smart IoT were analyzed and the future work of this system was proposed.